Major Trauma Triage Study (MATTS): Diagnostic accuracy of major trauma triage tools in English regional trauma networks – A case-cohort study - Gordon Ward Fuller; James Baird; Samuel Keating; Joshua Miller; Richard Pilbery; Natalie Scotney; Katherine McKnee; Janette Turner; Fiona Lecky; Antoinette Edwards; Andy Rosser; Rachael Fothergill; et al. (PLoS ONE, 2026)
Background Major trauma is a leading cause of death and disability. Specialised care in major trauma centres has been associated with improved outcomes and prehospital triage tools are used to ensure injured patients are treated in the right place and the right time. However, there is a trade-off between under- and over-triage, and this study aimed to externally validate current and newly developed major trauma triage tools. Methods A diagnostic case-cohort study was performed between November 2019 and February 2020 in 4 English regional trauma networks as part of the Major Trauma Triage Study (MATTS). The accuracy of 22 adult major trauma triage tools, including 3 newly developed MATTS tools was evaluated. Consecutive patients with acute non-trivial injury presenting to participating ambulance services were included and matched to data from the English national major trauma database. Theoretical accuracy was examined, with index tests assessed according to objective ambulance service data, regardless of the final triage decision or hospital destination. The primary reference standard was a consensus definition of serious injury that would benefit from expedited major trauma centre care. Results The case-cohort sample consisted of 2,607 patients, including 928 primary reference standard positive patients. The population weighted prevalence of major trauma meeting the primary reference standard definition was 3.1% (95% CI 2.3–4.0). Four optimally performing triage tools were identified with Pareto decision analysis: the Trauma score (sensitivity 0.1, specificity 0.99), MATTS specific tool (sensitivity 0.37, specificity 0.95), MATTS balanced tool (sensitivity 0.58, specificity 0.87), and the MATTS sensitive tool (sensitivity 0.72, specificity 0.76). This finding was unchanged in subgroup analyses of different age-groups and injury mechanisms; secondary analyses examining alternative reference standards (ISS ≥ 16, US consensus definition); and sensitivity analyses exploring missing data. Conclusions Four optimal triage tools, demonstrating a trade-off between sensitivity and specificity, were identified by this validation study. The choice of ideal tool will depend on prevalence of major trauma, and valuation of false positive and false negative cases. Further prospective investigation of real-life triage tool performance, including compliance and clinical judgment, is necessary.